Bidirectional triggering association between migraine and restless legs syndrome: A diary study. (April 2016) - Chen, Ping-Kun; Fuh, Jong-Ling; Wang, Shuu-Jiun
Objective: Migraine is comorbid with restless legs syndrome (RLS). However, the temporal association between these two episodic disorders remains elusive. The current study investigated the temporal relationship between migraine and RLS attacks. Methods: Migraine patients with RLS were recruited from a headache clinic. Patients with symptomatic RLS, RLS mimics, daily headaches, or daily RLS attacks were excluded. The patients recorded their headaches and RLS attacks for two weeks in a diary. The severity of each headache or RLS attack was rated on a four-point (0−3) Likert scale. Logit-normal, random-effects models were employed to estimate the odds ratios (ORs) for the temporal association between migraine and RLS attacks. Results: Thirty migraine patients with RLS (28 F/2 M, mean age 35.5 ± 9.0 years) completed the study. On the basis of 420 daily diary records, migraine attacks were associated with subsequent RLS attacks occurring on the same and next nights (OR = 6.94, 95% confidence interval (CI) = 4.39–11.0 and OR = 3.00, CI = 1.92–4.68; both p < 0.001). RLS attacks were associated with subsequent migraine attacks only on Day 1 (OR = 1.97 (CI = 1.3–2.98; p = 0.01). Overall, the frequencies of migraine and RLS attacks in two weeks were correlated (Spearman's correlation = 0.56, p = 0.001). Conclusions: Our study results showed a bidirectional triggering association between migraine and RLS attacks. The association was stronger and lasted longer for migraine triggering subsequent RLS than that for vice versa.